Penguatan Pelatihan Penerjemahan Bagi Penerjemah Pemula Sebagai Upaya Peningkatan Kualitas Penerjemah di Madura - Suryo Tri Saksono (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2013)
Novice translators in Madura are mostly less in translation competence since they only work as translators for tentative activity. They do not acknowledge that a translator is one of professions which involve multi competences. Translation training model which is done by translators in Madura tends to transfer only the structure of the Source Text into the Target Text. Translation process and translation strategy are not acknowledged as one of important aspects in translation training. Therefore, to be a professional translator, they have to master in accuracy, equivalent and faithfulness between Source Text and the Target Text in translation activity.